A Review of Current Status of Green Hydrogen Economy in Sub-Saharan Africa - Nnachi Gideon Ude; Richards Coneth Graham; Hamam Yskandar (IEEE Access)
Rapid increase in urbanization and industrialization due to increase in human population has led to increase in global warming resulting to climate change that affects the ecosystem. Unusual natural disasters such as cyclones, storms, floods, weather fluctuations, rising seal levels, transitional ecosystems and coastal disruptions are major adverse effects of climate change. There are huge worrisome concerns and uncertainties about the future of the planet earth due to climate change caused by high carbon emissions. Global aggressive policies in control of Carbon-dioxide ( $CO_{2}$ ) emissions from several combustion mechanisms have paved way for alternative/ clean energy sources. Green hydrogen is a promising means of clean energy sources for commercial power generation stations and other crucial systems such as hydrogen fuel cell vehicles (HFCVs), motors, drives, backup power for buildings, and also serving as a source of electrical energy for remote locations. The goal of this review paper is to review the current level of Sub-Saharan African nations’ preparedness to adopt green hydrogen as a way to mitigate local energy supply issues and strengthen their individual economies. The novelty of the paper is the light shedding on the progresses made by each member countries in SSA in terms of planning, funding, implementation, partnership and the gaps to be filled with regards to the production of green hydrogen in their local areas.